Recent Developments in the Work of the Investigating Judge under Algerian Code of Criminal Procedure Law No. 25-14" - Ahcene, Rafa Debbah; Azzeddine, Chouar; Soufiane, Goug; Kamel, Mehenni (The International tax journal, 2026)
The investigating judge, as the first degree of the investigation, is entrusted with several procedural tasks, through the search and investigation of evidence of proof or denial to show the truth in each criminal case in which the request for investigation has been submitted. The legislature has granted broad powers in this regard, but without prejudice to the individual rights and freedoms protected by the Constitution. The legislator has distinguished between the investigative work that is binding on the judge and which he may not delegate to others, and the investigative work in which he may delegate, and in all cases, the investigating judge must draw up a report thereof and send them together with the other documents.